Pembinaan Etika Komunikasi Melalui Media Sosial Yang Sesuai Dengan Hukum Yang Berlaku Pada Remaja Masjid Muhtarul Arifin Kota Batam - Kundori Kundori; Angel Purwanti; Irene Svinarky; Zikri Fachrul Nurhadi; Ummu Salamah (Universitas Garut, 2023)
pemSocial media is one part of new media that is used to inform anything to the public, whether used in business or interacting with others. Social media is one of the electronic media to communicate and do business by using internet media. Social media is most widely used by teenagers. Adolescents are individuals who have entered the stages of mental, emotional, social maturity and physical form. Although adolescents are said to be mature, but in relation to the use of social media, adolescents are often caught up in matters of privacy violations both as perpetrators and as victims. Therefore, understanding is needed in communicating properly and correctly in accordance with the ethics that apply to social media. The purpose of this community service is to help mosque teenagers use social media wisely and understand the limitations of conveying information on social media. As well as conducting training on how to write messages with communication ethics and not contrary to the law. The methods used are lectures, presentations, and direct practice. The teenagers were given the material then given the opportunity to practice. This service is carried out for 5 times according to the schedule that has been prepared. The results of this community service activity have implications for changing attitudes and increasing knowledge for mosque teenagers, who are expected to be much wiser in conveying, or disseminating information through social media. /emem/em/p